Respuesta :
(3x+−7y4)(3x+−7y4)=(3x)(3x)+(3x)(−7y4)+(−7y4)(3x)+(−7y4)(−7y4)=9x2−21xy4−21xy4+49y8=49y8−42xy4+9x
Answer:
9x² - 42xy⁴ + 49y⁸
Explanation:
The general rule in expanding a power 2 bracket is as follows:
(a-b)² = a² - 2ab + b²
Also note that:
(a^m)^n = a^(m*n)
Now, let's apply this to the given:
(3x - 7y⁴)²
(3x)² - 2(3x)(7y⁴) + (7y⁴)²
9x² - 42xy⁴ + 49y⁸
Hope this helps :)
9x² - 42xy⁴ + 49y⁸
Explanation:
The general rule in expanding a power 2 bracket is as follows:
(a-b)² = a² - 2ab + b²
Also note that:
(a^m)^n = a^(m*n)
Now, let's apply this to the given:
(3x - 7y⁴)²
(3x)² - 2(3x)(7y⁴) + (7y⁴)²
9x² - 42xy⁴ + 49y⁸
Hope this helps :)